A Companion to Augustine - Vessey, Mark (Blackwell Companions to the Ancient World, 2013)
A Companion to Augustinepresents a fresh collection of scholarship by leading academics with a new approach to contextualizing Augustine and his works within the multi-disciplinary field of Late Antiquity, showing Augustine as both a product of the cultural forces of his times and a cultural force in his own right.Discusses the life and works of Augustine within their full historical context, rather than privileging the theological context Presents Augustine’s life, works and leading ideas in the cultural context of the late Roman world, providing a vibrant and engaging sense of Augustine in action in his own time and place Opens up a new phase of study on Augustine, sensitive to the many and varied perspectives of scholarship on late Roman culture State-of-the-art essays by leading academics in this field